2017
DOI: 10.1016/j.ejop.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Grazing of Nuclearia thermophila and Nuclearia delicatula (Nucleariidae, Opisthokonta) on the toxic cyanobacterium Planktothrix rubescens

Abstract: During the last decades, the planktonic cyanobacterium Planktothrix rubescens became a dominant primary producer in many deep pre-alpine lakes. While altered physiochemical conditions due to lake warming seem to favour this cyanobacterial species, its dominance is partly attributed to factors conferring grazing resistance. The rigid structure of the cyanobacterial filaments and toxic secondary metabolites (e.g. microcystins) protect against diverse grazers. Nonetheless, species of the protistan genus Nuclearia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Nuclearia species are capable of growing in eutrophic and/ or contaminated environments. For example, they can ingest toxic filamentous cyanobacteria that can thrive in perturbed environments as their sole food source [29,41]. This capability appears to be related to their association with symbiotic bacteria that degrade toxic metabolites, as microcystin, contained in the cyanobacteria ingested by Nuclearia [28,29,67].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nuclearia species are capable of growing in eutrophic and/ or contaminated environments. For example, they can ingest toxic filamentous cyanobacteria that can thrive in perturbed environments as their sole food source [29,41]. This capability appears to be related to their association with symbiotic bacteria that degrade toxic metabolites, as microcystin, contained in the cyanobacteria ingested by Nuclearia [28,29,67].…”
Section: Resultsmentioning
confidence: 99%
“…For example, they can ingest toxic filamentous cyanobacteria that can thrive in perturbed environments as their sole food source [29,41]. This capability appears to be related to their association with symbiotic bacteria that degrade toxic metabolites, as microcystin, contained in the cyanobacteria ingested by Nuclearia [28,29,67]. Our N. pattersoni single cell was recovered by micromanipulation from the gut content of a dissected X. tropicalis tadpole grown in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to biological degradation in the water column. Studies have shown that zooplankton species have developed adaptive responses to co-exist with P. rubescens (Kurmayer and Jüttner 1999) and that certain eukaryotes including protists (e.g ciliates) are able to degrade the cyanobacterium and its toxin with the synergetic effect of specific bacteria (Dirren et al 2017). Thus, the absence of the cyanobacterium in the fossil record under low biomasses can be justified.…”
Section: Discussionmentioning
confidence: 99%